METHODS OF EVALUATION OF PRODUCTIVITY OF PROJECTS ON PROTECTION OF INFORMATION CHANNELS IN CORPORATE NETWORKS (Modern information system and technologies, 2018)
The article analyzes work on protection of channels in corporate networks. Considered the problems that arise when working on network protection. The use of different ways of protecting information is determined. Advice is given on how to protect against leakage and loss of information. The methods of estimation of work efficiency on protection of information channels in corporate networks are investigated.